2004
DOI: 10.1136/jech.2003.019307
|View full text |Cite
|
Sign up to set email alerts
|

Poorer self assessed health in a prospective study of men with screen detected abdominal aortic aneurysm: a predictor or a consequence of screening outcome?

Abstract: Study objectives: To assess the extent to which poorer self assessed health in men in whom an abdominal aortic aneurysm (AAA) is detected at screening is a consequence or a predictor of screening outcome. Design: Prospective study. Setting: Community based screening. Participants: 23 654 men who attended for AAA screening as part of the UK multicentre aneurysm screening study completed a measure of self assessed health before screening. A total of 1156 had an aneurysm detected. A sub-sample of screened men (57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Investigation of the accuracy of cause of death coding on the death certificates in the first 4 years of follow‐up was carried out by an independent mortality working party blinded to group allocation, and showed that inaccuracies in coding had a minimal impact on study outcomes5. The quality‐of‐life data collected in the trial around the time of screening showed no clear adverse (or beneficial) effects of screening, nor any long‐term effects after surgery5, 31.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the accuracy of cause of death coding on the death certificates in the first 4 years of follow‐up was carried out by an independent mortality working party blinded to group allocation, and showed that inaccuracies in coding had a minimal impact on study outcomes5. The quality‐of‐life data collected in the trial around the time of screening showed no clear adverse (or beneficial) effects of screening, nor any long‐term effects after surgery5, 31.…”
Section: Discussionmentioning
confidence: 99%
“…One general methodological problem is the lack of information on the level of distress before screening. This information is essential to assess whether distress after screening is a consequence of the screening procedure or existed before screening-as discussed in a study of distress in relation to screening for aortic aneurism (Marteau et al, 2004;McCaffery and Barrett, 2004). Another important question is whether the impact of screening on mental distress is modified by degree of information and support to the individual after screening (Connelly et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…No further adjustment is made to quality of life for those receiving positive screening results or undergoing AAA repair, as published evidence does not support long-term differences in quality-of-life outcomes in these groups. 21,22 Incremental life-years are estimated as life-years gained from a reduction in all-cause mortality.…”
Section: Methodsmentioning
confidence: 99%